A novel electrochemiluminescence biosensor based on S-doped yttrium oxide ultrathin nanosheets for the detection of anti-Dig antibodies. Issue 13 (6th June 2018) - Gao, Huan; Liu, Suli; Wang, Zhaoyin; Si, Ling; Dai, Zhihui
Abstract : The mechanism of a novel electrochemiluminescence biosensor based on S-doped yttrium oxide ultrathin nanosheets for detection of anti-Dig antibodies. Abstract : New S-doped yttrium oxide ultrathin nanosheets (NSs) were synthesized which had good electrochemiluminescence (ECL) properties. Through combining these NSs with small molecule linked DNA as the substrate, a novel ECL biosensor was constructed for the detection of protein biomarkers with an acceptable performance.